2022
DOI: 10.3390/ijms23020815
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Non-Coding RNAs in the Regulation of Virus Replication and Resultant Cellular Pathologies

Abstract: Non-coding RNAs, particularly lncRNAs and miRNAs, have recently been shown to regulate different steps in viral infections and induction of immune responses against viruses. Expressions of several host and viral lncRNAs have been found to be altered during viral infection. These lncRNAs can exert antiviral function via inhibition of viral infection or stimulation of antiviral immune response. Some other lncRNAs can promote viral replication or suppress antiviral responses. The current review summarizes the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…LncRNAs are found to be up- or down-regulated following TNF-α, LPS, IL-1β, IFN-α/β/γ treatment or after viral infection ( Carnero et al., 2016 ; Covarrubias et al., 2017 ; Liu et al., 2019 ; Barriocanal et al., 2022 ; Chen et al., 2022 ; Ghafouri-Fard et al., 2022 ). In our study, we predicted multiple putative NF-κB and STAT1 binding sites on the promoter region of the selected lncRNAs (LAP1-AS1, LINC21762, VAMP1-AS1, and ZAP-IT1) and experimentally demonstrated that both NF-κB and STAT1 were important for the up-regulation of the selected lncRNAs induced by IFN-β and ZIKV.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs are found to be up- or down-regulated following TNF-α, LPS, IL-1β, IFN-α/β/γ treatment or after viral infection ( Carnero et al., 2016 ; Covarrubias et al., 2017 ; Liu et al., 2019 ; Barriocanal et al., 2022 ; Chen et al., 2022 ; Ghafouri-Fard et al., 2022 ). In our study, we predicted multiple putative NF-κB and STAT1 binding sites on the promoter region of the selected lncRNAs (LAP1-AS1, LINC21762, VAMP1-AS1, and ZAP-IT1) and experimentally demonstrated that both NF-κB and STAT1 were important for the up-regulation of the selected lncRNAs induced by IFN-β and ZIKV.…”
Section: Discussionmentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs) were discovered decades ago and were identified as single-stranded RNA molecules that are more than 200 nucleotides [ 11 , 12 ]. Recently developed high-throughput sequencing revealed that thousands of lncRNAs were found to be highly/low expressed in a wide range of mammalian tissues.…”
Section: Introductionmentioning
confidence: 99%